Dietary lysine requirements of segregated early-weaned pigs - Owen, K.Q.; Richert, B.T.; Friesen, K.G.; Smith, J.W. II; Bergstrom, J.R.; Nelssen, Jim L.; Goodband, Robert D.; Tokach, Michael D.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A total of 320 (160 barrows and 160 gilts) 14- to 18-d-old pigs (initially 10.2 ± 2.2 lb) was used to determine the optimal level of dietary lysine needed for the segregated early-weaned pig. Two diet formulation methods were used with six dietary lysine levels within each formulation method, resulting in a 2 X 6 factorial arrangement of treatments. The first formulation method consisted of a basal diet that contained 1.95% lysine. Increasing levels of cornstarch replaced L-lysine to achieve the other five dietary treatments (1.2, 1.35, 1.50, 1.65, and 1.80% dietary lysine). All other amino acids in each diet were maintained at the same level as in the 1.95% lysine treatment. The second formulation method consisted of a basal diet (1.2% lysine) with the live additional treatments achieved by adding synthetic lysine and other essential amino acids to maintain an ideal amino acid ratio, relative to lysine. All diets contained 20% dried whey, 10% lactose, 7.5% spray-dried porcine plasma, 5.0% spray-dried wheat gluten, 5.0% select menhaden fish meal, 5.0% soybean oil, and 1.75% spray-dried blood meal. No lysine x formulation method interactions occurred for average daily gain (ADG) or average daily feed intake (ADFI) throughout the 28 d period. However, lysine x formulation method interactions were observed for feed efficiency (F/G) from d 0 to 7, d 0 to 14, and d 0 to 28. From d 0 to 7 postweaning, ADG was improved quadratically as dietary lysine increased and appeared to be maximized at 1.65% dietary lysine. Feed efficiency was lowest for pigs fed 1.80% lysine for the first diet formulation method and for pigs fed 1.95% lysine for the second diet formulation method. From d 0 to 14 postweaning, ADG and F/G were improved by increasing dietary lysine, with both response criteria maximized in pigs fed approximately 1.65% dietary lysine. However, ADFI was not affected during the 28-d experiment. These data suggest that segregated early-weaned pigs require approximately 5.2 and 6.2 g/d of lysine from d 0 to 7 and d 0 to 14 postweaning, respectively, to optimize growth performance. Based on these results, the diet for pigs < 11 lb needs to be formulated to contain at least 1.7% lysine. The transition diet (11 to 15 lb) should be formulated to contain approximately 1.5 to 1.6% lysine.
Keywords: Swine; Pigs; Requirements; Segregated early weaning